Proximate Compositions, Phenolic Compounds, Antioxidant Capacity and Antibacterial Activity of Chulta (Dillenia indica Linn.) Fruits: Effects of Maturity Stage and Extraction Solvent - Meeprathom, Dr. Natchanok Nukit; Jongrattanavit, Kankanit; Kooprasertying, Dr. Phakpoom (Journal of Food Health and Bioenvironmental Science, 2018)
Proximate compositions, phenolic compounds, antioxidant capacity and antibacterial activity were determined for chulta (Dillenia indica) fruits and the effects of maturity stage and extraction solvent were also investigated. Results revealed that fruit size and color values (a*, b*, C* and h˚) of immature and mature chulta fruits were significantly different. Immature fruits contained higher ash content but lower fat content compared to mature fruits. Immature chulta fruits also had higher total phenolic content in both water and ethanol extracts than mature fruits. Using HPLC-DAD/ESI-MS, 8 phenolic compounds (syringic acid O-hexoside, syringic acid, vanillic acid hexoside, (+)-catechin or (-)-epicatechin, procyanidin trimer type B, isoramnethin-3-O-hexoside, kaempferol-3,7-Ohexoside or luteolin-3,7-O-hexoside and luteolin-7-O-glucuronide) were tentatively identified in water extracts of chulta fruit, whereas only 3 phenolics (isoramnethin-3-Ohexoside, kaempferol-3,7-O-hexoside or luteolin-3,7-O-hexoside and luteolin-7-Oglucuronide) were found in ethanol extract. The results also showed that immature chulta fruits exhibited higher DPPH scavenging capacity and antibacterial potential against Escherichia coli and Staphylococcus aureus when compared to mature fruits. Finally, the results from this study could be used to encourage the utilization of chulta fruits as functional ingredients in healthy food or supplement production.